Cu2O Photocathode with Faster Charge Transfer by Fully Reacted Cu Seed Layer to Enhance Performance of Hydrogen Evolution in Solar Water Splitting Applications. Issue 17 (24th July 2019) - Jung, Kichang; Lim, Taehoon; Bae, Hyojung; Ha, Jun‐Seok; Martinez‐Morales, Alfredo A.
Abstract: In this work, we study the effect of Cu2 O film obtained from a fully reacted Cu seed layer as a photoelectrode in photoelectrochemical cells. The full reaction of the Cu layer shows an enhanced photocurrent density and improved efficiency in hydrogen evolution. The photocurrent density of textured Cu2 O (0.58 mA cm −2 at 0 V vs. RHE), without an unreacted Cu layer is two times higher than films containing an unreacted Cu layer (0.29 mA cm −2 at 0 V vs. RHE), under AM 1.5 illumination (100 mW cm −2 ). The thickness of the unreacted Cu layer influences significantly the charge transfer process at the interface between the Cu2 O and electrolyte. The enhanced photoelectrochemical performance of textured Cu2 O is attributed to the reduced charge recombination resulting from a longer carrier lifetime in the Cu2 O layer. Experimentally we confirmed that the unreacted Cu layer inhibits the photoelectrochemical performance of Cu2 O‐based photocathodes. The elimination of the unreacted Cu layer leads to higher photocurrent density. Abstract : CuOme on ! A 100 nm Cu2 O thin film synthesized via the full reaction of a Cu seed layer shows improved hydrogen generation reaction compared to Cu2 O with an unreacted Cu layer. A 100 % increment in photocurrent density is obtained by fully reacting the Cu seed layer.